Konsep Jiwa dalam Islam dan Tantangan Kesehatan Mental Modern: Pendekatan Komparatif Filosofis-Sufistik: The Concept of the Soul in Islam and Modern Mental Health Challenges: A Comparative Philosophical-Sufistic Approach - Azwar, Azwar; Muh. Amri; Nurman Said (Litera Academica Publishing, 2025)
This study aims to comprehensively examine the concept of the soul in Islamic thought through comparative, critical, and analytical approaches. The research focuses on four main objectives: (1) to explain the fundamental concept of the soul based on primary Islamic sources (the Qur’an and Hadith), (2) to compare the perspectives of prominent Islamic thinkers such as Ibn Sina, al-Ghazali, and Ibn ‘Arabi, (3) to analyze the differences between Islamic and Western approaches to understanding the soul, and (4) to offer a critique and propose a reconstruction of the concept of the soul relevant to contemporary contexts. This research employs a qualitative-descriptive method with a library research approach and content analysis techniques of classical and modern works. The findings reveal that the Islamic concept of the soul encompasses integrated spiritual, moral, and psychological dimensions, in contrast to the Western approach, which tends to be secular and materialistic. Furthermore, there are methodological differences among the philosophical, Sufi, and theological approaches in Islam, each offering a unique contribution to the understanding of the soul. The study concludes that reconstructing the Islamic concept of the soul requires integrating classical intellectual traditions with modern-day needs, particularly in addressing spiritual crises and mental health issues. Thus, the Islamic perspective on the soul offers a holistic alternative for character development and spiritual formation in human life.